Comparison of contrast induced nephropathy definitions and in-hospital mortality in patients undergoing primary percutaneous coronary intervention for acute myocardial infarction. (25th November 2020) - Jelic, D; Mehmedbegovic, Z; Milasinovic, D; Radomirovic, M; Pavlovic, A; Zobenica, V; Zaharijev, S; Vratonjic, J; Asanin, M; Vukcevic, V; Stankovic, G
Abstract: Background: Contrast induced nephropathy (CIN) has been associated with increased mortality in patients with acute myocardial infarction (AMI). However, different definitions of CIN have so far been used. Purpose: We aimed to compare predictive accuracy of the 2 contemporary CIN definitions in patients with AMI undergoing primary percutaneous coronary intervention (PCI). Method: From a high-volume, single-centre, prospective registry, in a period from 2009–2019, we identified 7987 pts who underwent primary PCI for AMI in whom creatinine measurements were available for analysis. CIN incidence was evaluated according to relative creatinine increases of ≥25% (CIN25) and ≥50% (CIN50) from baseline levels within 72 hours after intervention. The primary end point was in-hospital mortality. Results: Overall, 1116 (13.9%), and 345 (4.3%) patients developed CIN25, CIN50, respectively. Crude in-hospital mortality rate was 3.9% (312 pts) in the overall population. Both definitions were independently associated with in-hospital mortality (CIN25 adjusted odds ratio (OR) 4.2, 95% CI 2.7–6.6; p<0.001, and CIN 50 adjusted OR 8.2, 95% CI 4.9–13.9; p<0.001). Comparison of ROC curves showed that only the addition of the CIN50 (and not CIN25) definition to the combined model of clinical predictors of in-hospital mortality, which included pre-intervention TIMI flow 0–1, cardiogenic shock on admission, baseline creatinine clearance, prior stroke, chronic occlusion of non-culprit artery, post-intervention TIMI flow 3, left ventricular ejection fraction and procedure time, improved prognostic accuracy of the model (Figure 1). Conclusion: Only acute kidney injury according to the CIN50 definition, but not the CIN25 definition, offers additional prognostic information above and beyond the combination of baseline predictors of in-hospital mortality in patients with AMI undergoing primary PCI. Funding Acknowledgement: Type of funding source: None